A Study of Cytomegalovirus Serology among HIV-Infected Patients in the Highly Active Antiretroviral Therapy Era - Sufiawati, Irna; Widyaputra, Sunardhi; Djajakusumah, Tony S. (Faculty of Medicine, Universitas Padjadjaran, 2013)
Cytomegalovirus (CMV) is one of the most common opportunistic viruses in human immunodeficiency virus (HIV)-infected patients. The aim of this study was to determine the CMV seroprevalence among HIV-infected patients and investigate the correlation between the CMV immunoglobulin G (IgG) antibody titers and cluster of differentiation 4 (CD4) T-cell counts, as well as highly active antiretroviral therapy (HAART) use. Serum samples from 69 HIV-infected patients and 65 HIV-seronegative persons attending Dr. Hasan Sadikin General Hospital Bandung in March–June 2012 were examined to detect CMV IgG antibody using electrochemiluminescence immunoassay (ECLIA). Data were analyzed using chi-square test, t-tests and analysis of variance (ANOVA). The results show that there were no statistically significant differences in the seroprevalence of CMV between HIV-infected (97%) and HIV-seronegative persons (94%). The mean of CMV IgG antibodies titers in HIV-infected patients (335.39+174.87 U/mL) were significantly higher than that of HIV-seronegative persons (240.59+192.76 U/mL). There was no significant correlation between CMV IgG antibody titers and CD4 T-cell counts (the mean was 393.58+209.22 cells/mm3). The titers of CMV IgG antibodies were significantly inversely associated with HAART use. The mean of CMV IgG antibody titers in HIV-infected patients on HAART (335.41+172.98 U/mL) were significantly higher than patients without HAART (204.8+213.91 U/mL). In conclusions, this study confirms a high seroprevalence of CMV among HIV-infected patients. High titers of CMV are inversely associated with HAART use while no correlation with CD4 T-cell counts was found. [MKB. 2013;45(2):112–7]Key words: CD4, Cytomegalovirus (CMV), HAART, HIV, IgGStudi Serologi Cytomegalovirus pada Pasien yang Terinfeksi HIV di Era Highly Active Antiretroviral TherapyCytomegalovirus (CMV) adalah salah satu virus oportunistik yang paling umum pada pasien yang terinfeksi human immunodeficiency virus (HIV). Tujuan penelitian ini untuk mengetahui seroprevalensi CMV pada pasien HIV dan meneliti korelasi antara titer antibodi imunoglobulin G (IgG) CMV dan jumlah sel-T cluster diferensiasi 4 (CD4) serta penggunaan highly active antiretroviral therapy (HAART). Sampel serum dari 69 pasien HIV dan 65 HIVseronegatif yang berkunjung ke Rumah Sakit Dr. Hasan Sadikin Bandung pada bulan Maret–Juni 2012 diperiksa untuk mendeteksi antibodi IgG CMV dengan immunoassay electro chemiluminescence (ECLIA). Data dianalisis dengan menggunakan uji chi-kuadrat, t, dan analysis of variance (ANOVA). Hasil penelitian menunjukkan tidak ada perbedaan yang signifikan antara seroprevalensi CMV pada pasien HIV (97%) dan HIV-seronegatif (94%). Titer antibodi rata-rata IgG CMV pasien HIV (335,39+174,87 U/mL) signifikan lebih tinggi daripada HIV-seronegatif (240,59+192,76 U/mL). Tidak ada hubungan yang signifikan antara titer antibodi IgG CMV dan jumlah sel-T CD4 (rata-rata 393,58+209,22 sel/mm3). Titer antibodi IgG CMV secara signifikan berhubungan terbalik dengan penggunaan HAART. Titer antibodi IgG CMV rata-rata pasien HIV dengan HAART (335,41+172,98 U/mL) signifikan lebih tinggi dibandingkan dengan pasien tanpa HAART (204,8+213,91 U/mL). Simpulan, penelitian ini menegaskan seroprevalensi CMV pasien HIV dan titer antibodi IgG CMV yang tinggi berhubungan terbalik dengan penggunaan HAART tetapi tidak berkorelasi dengan sel-T CD4. [MKB. 2013;45(2):112–7]Kata kunci: CD4, Cytomegalovirus (CMV), HAART, HIV, IgG DOI: http://dx.doi.org/10.15395/mkb.v45n2.114